Internalisasi Nilai Hukum dan Pembentukan Budaya Taat Hukum: Perspektif Tanggung Jawab Kewargaan dan Islamic Sociological Jurispondence Theory - Ahmad Muhammad Mustain Nasoha; Retna Khoiriyah; Maulida Akmasa Moza Hidayat; Alfi Farras Najwa Sabiel; Nafisa Syahla Zaidah (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the process of internalizing legal values in the formation of a culture of law-abidingness by emphasizing the perspective of civic responsibility and the Islamic Sociological Jurisprudence Theory approach. The main problem studied is how legal values are not only understood normatively, but also internalized in the individual and collective consciousness of society, thus giving rise to sustainable law-abiding behavior. The research method used is a normative juridical approach with strengthening conceptual and sociological analysis of legal dynamics in society. The results show that the internalization of legal values is a multidimensional process involving cognitive, affective, and spiritual aspects, which are influenced by education, the social environment, role models, and the consistency of law enforcement. In the context of civic responsibility, a culture of law-abidingness is not only formal compliance with regulations, but also reflects moral awareness and active participation of citizens in maintaining social order. Meanwhile, Islamic Sociological Jurisprudence Theory offers an integrative paradigm that combines the normative dimensions of sharia with social reality, through a comparative approach of schools of thought, maqāṣid al-syarī‘ah, and an orientation toward the welfare of the people. This research emphasizes that the formation of an effective culture of law-abidingness requires a holistic and contextual approach, in which law is understood as a living and adaptive social instrument. Thus, the internalization of legal values based on civic responsibility and an Islamic sociological jurisprudence approach can encourage the realization of substantive justice, high legal awareness, and a civilized and sustainable social order.